2019
DOI: 10.1021/acs.energyfuels.9b02607
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Recycling of Automotive Shredder Residue by Chemical-Looping Gasification Using the Generated Ash as Oxygen Carrier

Abstract: Recycling of the carbon atoms from plastic waste is a crucial step in establishing a circular economy. The intense sorting required to produce easily treatable streams inevitably produces highly heterogeneous waste byproducts, which are challenging to recycle. In this paper, we propose that automotive shredder residue (ASR), which is one such heterogeneous waste, can be recycled by chemical-looping gasification (CLG), using its own ash as the oxygen-carrying bed material. We investigate two critical issues reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
4
14
0
Order By: Relevance
“…Other compounds that were identified as having minor contributions to the oxygen transport were Ni, Mn, and Cu. The study of Pissot et al 7 also showed that the presence of S in the ash could further add to the oxygen carrying through cycles of CaSO 4 /CaS, as described earlier. 37 Thus, that study 7 confirmed the beneficial effects of the inherent oxygen carriers accrued from the ASR ash interaction with the bed material under CLG conditions.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…Other compounds that were identified as having minor contributions to the oxygen transport were Ni, Mn, and Cu. The study of Pissot et al 7 also showed that the presence of S in the ash could further add to the oxygen carrying through cycles of CaSO 4 /CaS, as described earlier. 37 Thus, that study 7 confirmed the beneficial effects of the inherent oxygen carriers accrued from the ASR ash interaction with the bed material under CLG conditions.…”
Section: Introductionmentioning
confidence: 55%
“…The oxygen partial pressure for the oxidizing condition in the boiler was assumed to be 0.2 atm. In the gasifier, the partial pressure of oxygen was calculated to be on the order of magnitude of 1 × 10 −18 atm, given the composition of permanent gases leaving the gasifier, as reported by Pissot et al, 7 where the gas composition of the same experiment was investigated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the existing thermochemical processes, dual fluidized bed (DFB) gasification presents a number of attractive features, including its flexibility in terms of fuel input, high heat- and mass-transfer rates, homogeneous temperature profile, and the production of raw gas not diluted with nitrogen, without the need for producing pure oxygen. DFB gasifiers have been tested at the industrial scale with biomass and at the semi-industrial ,, and pilot , scales with plastic waste. As shown in Figure , a DFB gasifier consists of two interconnected reactors: a gasifier, in which the fuel reacts with steam to form a raw gas, and a combustor, where part of the char from the fuel is burnt to produce the heat required for the gasification reactions, with the char and heat being transported by the bed material that circulates between the two reactors.…”
Section: Introductionmentioning
confidence: 99%